Spatial and Temporal Variation of Scheduled Caste and Scheduled Tribe Population in Different Arid Districts of Western Rajasthan - Gupta, B S; Chand, Roop (Annals of Arid Zone, 2016)
The scheduled castes and scheduled tribes together contribute 21.5% of the total population in western Rajasthan. In 1991 census, wide variation was observed in the spatial distribution of scheduled caste and scheduled tribe population and population density in different arid districts. Location quotient method has been used in order to study the concentration of scheduled caste and scheduled tribe population within the study region. Seven districts, namely Churu, Ganganagar, Nagaur, Sikar. Jhunjhunu, Jalor and Pali are the areas of high concentration of scheduled castes whereas, Jaisalmer, Bikaner and Banner districts are the areas of low concentration. Areas of high concentration of tribal population are Barmer, Jodhpur, Sikar, Jhunjhunu, Jalor and Pali. Here 90.8% of tribal population of western Rajasthan resides. Jaisalmer, Dikaner, Churu, Ganganagar and Nagaur recorded low concentration. where 9.2% of the entire scheduled tribe population resides. Scheduled caste density follows total population density. Jhunjhunu has highest scheduled caste population density (41), whereas, Jaisalmer has minimum (1) population density. In the entire western Rajasthan, the density of tribal population is highest in Jalor (9.1) and least in Bikaner (0.1).